2020
DOI: 10.3389/fpsyg.2020.01198
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness, Age, and Multiple Aspects of Executive Function Among Preadolescent Children

Abstract: Cardiorespiratory fitness (CRF) and age have been positively associated with children's executive function; however, few studies have simultaneously assessed the associations between both variables and different aspects of executive function among preadolescent children. Therefore, the purpose of the current study was to evaluate the simultaneous influence of CRF and age on three aspects of executive function. Preadolescent children's (n = 338) CRF levels were estimated based on the Progressive Aerobic Cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
(66 reference statements)
4
15
1
Order By: Relevance
“…In addition, our data revealed no association between fitness and mean RT. This finding, although contradictory with studies using field-based fitness assessments (e.g., PACER), which found a relationship between greater fitness and shorter mean RT across congruency trials (Scudder et al, 2014: Zhan et al, 2020, is in alignment with research employing gold-standard fitness assessments (i.e., VO 2peak ) and found a selective relationship of fitness with response accuracy (Berchicci et al, 2015;Pontifex et al, 2011;Raine et al, 2018;Wu et al, 2011). Moreover, our data on SDRT and CVRT indicated that higher fitness is associated with smaller response variability during congruent trials.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In addition, our data revealed no association between fitness and mean RT. This finding, although contradictory with studies using field-based fitness assessments (e.g., PACER), which found a relationship between greater fitness and shorter mean RT across congruency trials (Scudder et al, 2014: Zhan et al, 2020, is in alignment with research employing gold-standard fitness assessments (i.e., VO 2peak ) and found a selective relationship of fitness with response accuracy (Berchicci et al, 2015;Pontifex et al, 2011;Raine et al, 2018;Wu et al, 2011). Moreover, our data on SDRT and CVRT indicated that higher fitness is associated with smaller response variability during congruent trials.…”
Section: Discussioncontrasting
confidence: 87%
“…Of note, the current literature indicates a link between increased cardiorespiratory fitness and brain health in children, with a small to moderate relationship of cardiorespiratory fitness on inhibitory control at a cognitive/attention level (Berchicci et al., 2015; Raine et al., 2018; Scudder et al., 2014; Wu et al., 2011; Zhan et al, 2020). Inhibitory control refers to the cognitive ability to withhold an individual's attention to respond to irrelevant but prepotent information and stay focused on goal‐relevant information (Diamond, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies using laboratory-based and filed-based CRF assessments have indicated positive associations between CRF and task performance involving response inhibition in preadolescent children [ 15 ] and young adults [ 16 , 17 ]. Finally, similar positive links between CRF and working memory [ 11 , 18 ] and shifting [ 18 , 19 ] aspects of EF have been reported.…”
Section: Introductionsupporting
confidence: 71%
“…Cardiorespiratory fitness (CRF) may also affect various aspects of EF [ 11 , 12 ]. Cross-sectional research has revealed a positive relationship between CRF and the performance of the tasks involving interference aspect of inhibition in late-middle-aged [ 13 ] and older adults [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strategic planning and the organization of goal-directed behavior seem to be fully developed between the ages of 20 and 29 (De Luca et al, 2003). Zhan et al (2020) proved that children with higher levels of cardiorespiratory fitness and children of a higher age are generally associated with advanced working memory inhibitory control and shifting aspects of executive functions. Older soccer players should outperform younger players with less developed prefrontal structures and less experience in perceiving relevant information.…”
Section: Introductionmentioning
confidence: 99%